Sexuality in Rehabilitation: Supporting Canadian Practitioners Conceptually Towards Client Enablement - Reel, Kevin; Davidson, Sylvia (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
This article explores the many dimensions of sex which result in very strong moral and ethical responses. In support of practitioners who wish to feel more comfortable and competent discussing sexual matters, the article then introduces a hybrid conceptual model of practice. Combining one model originally from sexology and another from occupational therapy, the Ex-PLISSIT Enablement Model offers a flexible, progressively-staged framework to guide practitioners toward a plan to better understand and work within their own scope while also assessing if clients are ready and willing to engage with the subject to varying degrees.